2013
DOI: 10.1002/hep.26458
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B infection in adolescents vaccinated at birth: An alarm bell in favor of the need for a booster?

Abstract: et al. 1 reported that a significant proportion of adolescents born to hepatitis B surface antigen (HBsAg)-positive mothers, who had postnatal hepatitis B immune globulin (HBIG) and hepatitis B vaccine, lost immune memory and developed a HBsAg carrier state. Having maternal hepatitis B e antigen (HBeAg) positivity was the most important determinant for developing chronic hepatitis B.Vaccination has proved to be highly effective in preventing and controlling hepatitis B, carrier rate, and hepatitis B virus (HBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In several recent studies, researchers reported that about one-quarter of neonatal vaccine recipients had lost their immune memory to the HBV vaccines when entering young adulthood [37] , [38] . Because young adults may engage in risky behaviors that potentiate horizontal transmission of HBV as they become sexually active [31] , the booster policy was recently recommended for consideration in highly endemic regions, such as some Asian countries [39] . Our current study showed that a booster at age 10–14 years might improve the neonatal vaccinee's immunological memory and potentially prevent HBV horizontal infection in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…In several recent studies, researchers reported that about one-quarter of neonatal vaccine recipients had lost their immune memory to the HBV vaccines when entering young adulthood [37] , [38] . Because young adults may engage in risky behaviors that potentiate horizontal transmission of HBV as they become sexually active [31] , the booster policy was recently recommended for consideration in highly endemic regions, such as some Asian countries [39] . Our current study showed that a booster at age 10–14 years might improve the neonatal vaccinee's immunological memory and potentially prevent HBV horizontal infection in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…These observations led to the conclusion that protection against clinically significant breakthrough infection and chronic carriage is long-term rendering booster doses unnecessary [1,[9][10][11]. However, over the past years, a number of studies have reported about waning immunity over time by showing a loss of the ability to respond to booster vaccination [12][13][14][15][16]. A recent meta-analysis has shown that, 20 years after infant vaccination, about 40% of individuals who had lost protecting antibodies did not respond to booster vaccination [17].…”
Section: Introductionmentioning
confidence: 99%
“…Because Hexavac HBsAg content was only 5 μg, the possibility that children who received this vaccine could be at higher risk of losing immune memory and developing infections of HBV in adolescence or in adulthood cannot be excluded. On the other hand, recent studies showed that immune memory may diminish during the second decade post‐vaccination (particularly in children vaccinated at birth), suggesting the need for a booster dose during adolescence . Wu et al showed that 15% of adolescents born to HBsAg/HBeAg‐positive mothers who received primary infantile vaccination developed chronic HBV infection.…”
Section: Hexavacmentioning
confidence: 99%